Torsade de pointes associated with encephalitis - Alehan, Dursun; Ceviz, Naci; Çeliker, Alpay (The Turkish Journal of Pediatrics, 1999)
Torsade de pointes is a polymorphic ventricular tachycardia. Causes of torsade de pointes are well described. Although intracranial disease can produce dramatic electrocardiographic (ECG) changes, we are not aware of previous cases with torsade de pointes and encephalitis. We report a case with encephalitis who developed torsade de pointes, and was treated with temporary ventricular pacing and magnesium infusion.